IMPLEMENTASI PROGRAM KEAGAMAAN DALAM MENINGKAT KARAKTER RELIGIUS SISWA KELAS VIII DI SMP NEGERI 1 JATIREJO - Dimas Ageng Saputra (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2026)
This study aims to describe the implementation of a religious program to improve the religious attitudes of eighth-grade students at SMP Negeri 1 Jatirejo. This research was motivated by concerns about the moral decline of the younger generation, as evidenced by various negative actions within the school environment. Through the implementation of the religious program, it is hoped that students' personalities will develop in harmony with religious values. In this study, a descriptive qualitative approach was applied with data collection techniques through observation, in-depth interviews, and documentation. Data sources included the principal, Islamic Religious Education teachers, and eighth-grade students. The research findings revealed that religious programs at SMP Negeri 1 Jatirejo were conducted routinely, including congregational Dhuhr prayers, Quran memorization, istighasah prayers, hadrah, short Islamic boarding schools, and commemoration of Islamic holidays. The program's implementation went well because it was supported by effective school management, adequate facilities, and the involvement of all school members. Religious programs play a vital role in shaping students' religious character, encompassing faith, religious practice, noble character, and religious knowledge. However, their implementation still faces several challenges, such as low levels of awareness among some students and minimal involvement from several relevant parties. The program's success is supported by close collaboration between teachers and school management, as well as the availability of adequate facilities. However, obstacles encountered include a lack of individual discipline and technical issues in operational implementation. This study reveals that the religious program implemented at SMP Negeri 1 Jatirejo has successfully strengthened students' religious character. However, ongoing efforts are needed to address ongoing challenges. These findings are expected to contribute to both the theoretical and practical aspects of religious character formation in the school environment.